W.S. Merwin’s Search for Walt Whitman, Whoever He Was - Ed Folsom (Transatlantica)
This essay recounts the author’s decades-long conversations with W.S. Merwin about Walt Whitman. Critics have long assumed that Merwin had a primarily negative attitude toward Whitman’s poetry, viewing him as a spokesperson for the U.S.’s embrace of manifest destiny and its catastrophic ecological impact. Some of Merwin’s dismissive attitude toward Whitman was inherited from two of Merwin’s acknowledged poetic mentors, Ezra Pound and T.S. Eliot, who both also had mostly negative attitudes toward Whitman. The essay argues, however, that both Pound and Eliot had somewhat hidden reserves of admiration for Whitman, and that the same is true of Merwin. The essay examines those aspects of Whitman that Merwin was both attracted to and influenced by—those moments when Whitman spoke of the grass and those moments when Whitman confronted silence and wordlessness—and analyzes Merwin’s poems “A Contemporary” and “Whoever You Are” as direct responses to Whitman, places where Merwin records his deep and intimate engagement with Whitman.